Analysis of Road Defects Using the Bina Marga Method on The Sukadana-Teluk Batang Road Section - Yunri, Donatus Andasi; Basalim, Said; Mayuni, Siti (Jurnal Teknik Sipil, 2024)
The Sukadana-Teluk Batang road section supports community mobility and economic activities in Kayong Utara Regency. However, the road suffers significant damage due to excessive vehicle loads, poor drainage, environmental influences, and insufficient maintenance. This study analyzes road conditions using the Bina Marga method, which categorizes and evaluates damage types like cracks, potholes, and rutting to determine severity and prioritize maintenance. The results indicate that 30.69% of the road area is damaged, with critical segments such as STA 31+200 and STA 32+000 requiring immediate improvement. Segments with moderate damage are allocated for periodic maintenance, while minimal defects are addressed through routine maintenance. The study also integrates visual tools like graphs and maps to highlight damage distribution and facilitate decision-making. By emphasizing a data-driven approach, this research provides practical solutions for optimizing maintenance resources, extending road lifespan, and supporting sustainable regional development. The findings contribute to civil engineering practices and serve as a reference for managing infrastructure in similar regions.